Pengaruh Media Pengajaran dalam Peningkatan Partisipasi Belajar Peserta Didik pada Proses Belajar Asynchronous pada Kelas Inklusi : [The Influence of Teaching Media on Improving Student Participation in Asynchronous Learning in Inclusive Classes] - Dinda Nurlia Pratiwi; Prinastining Dyah Wigati; Robinson Leonardo Ticoalu (Universitas Pelita Harapan, 2024)
Every individual, including students with special needs or those with exceptional intelligence, has the same right to education. Unfortunately, many educators still lack sufficient awareness about this phenomenon. As a result, issues in the classroom related to students with special needs are often not adequately addressed. Therefore, the solution to this challenge is inclusive education. The implementation of inclusive education can help students develop their potential to the fullest. This study aims to provide basic knowledge about inclusive education to graduate students of Universitas Pelita Harapan, class of 52, through interactive learning on Google Classroom. The research uses a qualitative approach, with 18 respondents who are expected to identify early signs if one of their students shows special characteristics. The findings of the study show that the completion rate of tasks in the inclusive classroom did not fully reach 100%, indicating that some participants did not complete their assignments. However, participation in the inclusive classroom remained high, with a minimum task completion rate of 80.3%. The use of interactive and varied learning media can facilitate the development of various types of intelligence in students, creating a more inclusive and empowering learning environment.